Fire, people and reindeer in the boreal forest : the role of fire in the historical and contemporary interactions between Sami reindeer herding and forest management in northern Sweden - Cogos, Sarah (HAL CCSD, 2020)
In the boreal forest of northern Sweden, fire was used from around 1920 to 1970 as a forest regeneration measure, and then abandoned for some decades. Since the 1990s, fire restoration has been carried out through regeneration and conservation burning in commercial and protected forests. The same forest is also used as reindeer pasturelands by indigenous Sami herders. The overall aim of this thesis was to investigate the human dimensions of fire regimes in the Swedish boreal forest, with a focus on interactions between fire, Sami reindeer husbandry and forest management during the 20th century and up to the present. This goal was addressed through an interdisciplinary approach combining historical ecology and environmental anthropology. The results show that while forest managers conceive fire as a natural perturbation, Sami herders have conflicting feelings about fire, as they have had to endure the effects of imposed burning strategies on their livelihood. While burning can promote summer pasture and maintain the long-term availability of winter pasture, it destroys lichen pasture temporarily and Sami ecological knowledge shows that burning also affects the behaviour and movement patterns of the reindeer. These pitfalls already affected reindeer herding during the first half of the 20th century, and even triggered an early form of consultation with the forestry sector. Today, while generally opposed to all external measures that affect reindeer grazing grounds, Sami herders increasingly see in burning a way to restore winter pasturelands. They use the consultation process with forest owners to negotiate for burning that serves their interests. The fire regime thus reflects a combination of technical constraints, forest management and nature conservation objectives, and conditions posed by Sami herders. However, in order for Sami herders to actually assert their interests, true fire co-management would have to be implemented. Dans le nord de la Suède, le feu a été utilisé comme mesure de régénération ...